2013
DOI: 10.13102/scb323
|View full text |Cite
|
Sign up to set email alerts
|

Estabelecimento in vitro e crescimento inicial de Physallis angulata (Solanaceae)

Abstract: Resumo -O objetivo deste estudo foi estabelecer Physalis angulata in vitro e identificar o meio de cultura mais adequado para a germinação e crescimento inicial da espécie. Nós avaliamos a germinação, o estabelecimento in vitro e o crescimento inicial de suas plântulas em diferentes meios de cultura (MS, WPM e ½MS). Primeiro, foram avaliados porcentagem, tempo médio e índice de velocidade de germinação 15 dias após a inoculação das sementes. Em seguida, foram avaliados número médio de raízes e folhas, comprime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…The results of the germination speed index (GSI), under the absence of light, were not only higher than those obtained under the other light conditions, but was also higher than those obtained in other studies with P. angulata under white light (LANNA et al, 2013;OLIVEIRA et al, 2013). On the other hand, the GSI values obtained by Souza, Souza, and Pelacini (2011) and Oliveira et al (2013) are consistent with those observed in this study under white light.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The results of the germination speed index (GSI), under the absence of light, were not only higher than those obtained under the other light conditions, but was also higher than those obtained in other studies with P. angulata under white light (LANNA et al, 2013;OLIVEIRA et al, 2013). On the other hand, the GSI values obtained by Souza, Souza, and Pelacini (2011) and Oliveira et al (2013) are consistent with those observed in this study under white light.…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, light at far-red frequency (FR) caused lower results for most of the variables analyzed. With seeds of P. angulata, in the presence of light, Carvalho et al (2014) and Oliveira et al (2013) obtained germination above 80%. However, the results of this study do not allow the seeds of this species to be classified as positive photoblastic.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations